Return-to-health effect of modern combined antiretroviral therapy potentially predisposes HIV patients to hepatic steatosis. Issue 17 (April 2018) - Mohr, Raphael; Boesecke, Christoph; Dold, Leona; Schierwagen, Robert; Schwarze-Zander, Carolynne; Wasmuth, Jan-Christian; Weisensee, Insa; Rockstroh, Jürgen Kurt; Trebicka, Jonel
Abstract : Abstract: Prevalence and risk factors for hepatic steatosis (HS) in the human immunodeficiency virus (HIV)-positive population of western countries are controversially discussed and potentially confounded by coinfection with viral hepatitis. Significant HS (more than 10% of hepatocytes) can be accurately assessed using controlled attenuation parameter (CAP) determination. Aim of this study was to assess prevalence and factors associated with significant HS in HIV monoinfected patients. A total of 364 HIV-infected patients (289 monoinfected) were included in this prospective, cross-sectional study. All patients underwent CAP determination. Steatosis was classified as S1 (significant steatosis) with CAP > 238 dB/m, S2 with CAP > 260 dB/m, and S3 with CAP > 292 dB/m. Multivariable logistic regression analyses were performed to assess the factors associated with HS in this cohort. Significant HS was detected in 118 monoinfected patients (149 in the total cohort). In the total cohort as well as in the monoinfected patients alone, HS grade distribution showed a similar pattern (S1:29%, S2:34%, and S3:37%). Interestingly, patients with HS had a longer history of HIV infection and combined antiretroviral therapy (cART). Interalia, age, gender, ethnicity, and metabolic factors were strongly associated with HS, while body mass index (BMI), triglyceride, and glycated hemoglobin (HbA1c) levels were independently associated with significant HS. HS is highly prevalent among HIV monoinfected patients. Although metabolic risk factors, such as obesity and poorly controlled diabetes, are independently associated with HS in HIV monoinfected patients, cART and control of HIV seem to play an indirect role in the development of HS, probably through the return-to-health effect. Abstract : Supplemental Digital Content is available in the text